Cross‐cultural differences in eyewitness memory reports. Issue 2 (5th February 2020) - Anakwah, Nkansah; Horselenberg, Robert; Hope, Lorraine; Amankwah‐Poku, Margaret; van Koppen, Peter J.
Summary: Increasingly, investigators conduct interviews with eyewitnesses from different cultures. The culture in which people have been socialised can impact the way they encode, remember, and report information about their experiences. We examined whether eyewitness memory reports of mock witnesses from collectivistic (sub‐Saharan Africa) and individualistic (Northern Europe) cultures differed regarding quantity and quality of central and background details reported. Mock witnesses (total N = 200) from rural Ghana, urban Ghana, and the Netherlands were shown stimuli scenes of crimes in Dutch and Ghanaian settings and provided free and cued recalls. Individualistic culture mock witnesses reported the most details, irrespective of detail type. For each cultural group, mock witnesses reported more correct central details when crime was witnessed in their own native setting than a non‐native setting, though for different recall domains. The findings provide insight for legal and investigative professionals as well as immigration officials eliciting memory reports in cross‐cultural contexts.